2021
DOI: 10.1002/acn3.51275
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical short‐term plasticity elicited by deep brain stimulation

Abstract: Objective To investigate local short‐term neuroplasticity elicited by subthalamic, thalamic, and pallidal deep brain stimulation (DBS) for movement disorders. Methods During DBS surgery, we delivered pairs of stimulus pulses with both circular and directional leads across 90 interstimulus intervals in 17 participants and recorded local field potentials from unused contacts on the implanted electrode array. We removed the stimulus artifact, validated the neural origin of the underlying signals, and examined sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Paired pulse studies are a well-established method for evaluating inhibitory and facilitatory mechanisms (Kujirai et al, 1993 ; Kobayashi and Pascual-Leone, 2003 ; Prescott et al, 2013 ). A prior paired pulse study evaluated the short-latency components (<10 ms) in the STN, pallidum, and thalamus across Parkinson's disease and essential tremor patients and argued that DBS paired pulses can facilitate short-term plasticity and enhance communication between nodes in the BGTC circuit (Awad et al, 2021 ). Their findings suggest that the short-latency evoked resonant activity (occurring before 10 ms) in the STN was maximal when IPIs were >1 ms apart and peaked around 2 ms. We demonstrated that changes in long-latency components in the STN-EP were significant when pulses were spaced 2 ms apart, suggesting that IPIs in that range may best facilitate neural pathways responsible for both the short and long latency components in the STN-EP.…”
Section: Discussionmentioning
confidence: 99%
“…Paired pulse studies are a well-established method for evaluating inhibitory and facilitatory mechanisms (Kujirai et al, 1993 ; Kobayashi and Pascual-Leone, 2003 ; Prescott et al, 2013 ). A prior paired pulse study evaluated the short-latency components (<10 ms) in the STN, pallidum, and thalamus across Parkinson's disease and essential tremor patients and argued that DBS paired pulses can facilitate short-term plasticity and enhance communication between nodes in the BGTC circuit (Awad et al, 2021 ). Their findings suggest that the short-latency evoked resonant activity (occurring before 10 ms) in the STN was maximal when IPIs were >1 ms apart and peaked around 2 ms. We demonstrated that changes in long-latency components in the STN-EP were significant when pulses were spaced 2 ms apart, suggesting that IPIs in that range may best facilitate neural pathways responsible for both the short and long latency components in the STN-EP.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies reported such subcortical rewiring mechanisms for skill learning such as second language and motor training (Lui et al, 2020; Sampaio-Baptista et al, 2013; Scholz et al, 2009). A recent study also indicates subcortical short-term plasticity yielded by deep brain stimulation pulse (Awad et al, 2021). All these observations are agreeing with the frustrating essence of the brain subcortex.…”
Section: Discussionmentioning
confidence: 98%
“…So controlling the activation of frustrating subcortical regions can provide the favorable systemic reorganization of the brain network. It may be appliable by focusing on our detected frustrating regions and connections using sophisticated subcortical stimulation methods (Awad et al, 2021; Colle et al, 2021; Folloni et al, 2019; Shi et al, 2021). In addition, the prominent role of the subcortex in frustration formation may be related to its unidirectional projections (Shi et al, 2014) or indirect pathways (Lanciego et al, 2012) which need more exploration.…”
Section: Discussionmentioning
confidence: 99%
“…For this superposition or temporal summation to be effective, the intra-burst period of the pulse trains must be greater than the refractory period of the neuronal population being stimulated with the electrical pulses. If the inter-pulse period is smaller than the refractory period of the neural circuitry being activated, a temporal summation of evoked responses is not expected to occur (19, 21, 22). Pulse amplitude modulation can be employed, in addition or instead of frequency modulation, to adjust the evoked responses’ amplitude and suppress the spontaneous oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that adjustments in the stimulation pulse frequency and amplitude are needed to create precise destructive or constructive interference between stimulation-evoked responses and spontaneous oscillations whose amplitude envelope varies over time. Pulse frequency modulation results in changes in the evoked response amplitude because of the principle of superposition (or temporal summation) observed in responses to stimulation trains (18)(19)(20). For this superposition or temporal summation to be effective, the intra-burst period of the pulse trains must be greater than the refractory period of the neuronal population being stimulated with the electrical pulses.…”
Section: B Pulse Frequency Amplitude and Phase Modulation Mediate Opt...mentioning
confidence: 99%